Peran Komitmen Organisasi, Disiplin Kerja dan Iklim Kerja Terhadap Kinerja Pegawai: Studi BKD Papua Barat - Yohanes D. Resi; Mattalatta; Ansar; Kurniawaty (Cerdika: Jurnal Ilmiah Indonesia, 2025)
This research aims to analyze the role of Organizational Commitment, Work Discipline and Work Climate on Employee Performance at the Regional Civil Service Agency of West Papua Province. This research uses a quantitative approach, data collection uses a questionnaire, with a sample size of 60 respondents. Data analysis uses multiple linear regression, hypothesis testing is carried out using partial, simultaneous and dominant tests (Beta test). The research results show that Organizational Commitment, Work Discipline and Organizational Commitment play a positive and significant role in improving employee performance; Work discipline plays the most dominant role in employee performance at the West Papua Province Regional Civil Service Agency.